Končniški in mešani naglasni tip samostalnikov a-jevske sklanjatve v nadiškem narečju slovenščine - Šekli, Matej (Slavistična revija, 2007)
The article discusses the desinential and mobile accent pradigms of a-stem nouns in the Nadiško (Nadiža/Natisone) dialect of Slovene, from the point of view of (historical) comparative Slavic linguistics. The presence of two subtypes of the desinential accent paradigm points to the preservation of a Slavic accentual archaism in Slovene, i.e., the distinction between the reflexes of Proto-Slavic accent paradigms b in c in the nouns with a Proto-Slavic short vowel in the one syllable stem.
Keywords: accentology; a-declension; a-jevska sklanjatev; desinential accent paradigm; Jevšček; končniški naglasni tip; mešani naglasni tip; mobile accent paradigm; morphological accent paradigms; nadiško narečje; naglasoslovje; Natisone dialect; oblikotvorni naglasni tipi; samostalnik; Slovene dialectology; Slovene language; slovenska narečja; slovenščina